Integrated self-report and observational risk assessment for work-related musculoskeletal disorder in small and medium enterprises - Mohamad, Effendi; Okka Adiyanto; Muhammad Faishal; Jaafar, Roshidah; Mohamad, Nor Akramin; Abd Razak, Jeefferie; Mulaicin, Mutia (Faculty of Engineering, Khon Kaen University, Thailand, 2021)
Musculoskeletal Disorder (MSD) is a very common grievance of employees working with SMEs and large industries. The objective of this research is to examine the risk of MSD for operators in the manufacturing segment of SMEs by deploying two ergonomic approaches: self-report (SR) and observation method (OM). The project has been executed in the manufacturing SMEs in Indonesia. The SR methodology utilizes the Nordic Body Map (NBM) for assessing the comfort and grievances of the operator. Besides, the OM methodology deploys the Rapid Upper Limb Assessment (RULA) as an appraisal of the worker’s work stance. A Self Report evaluation based on NBM triggered the obtained concerns in the upper body that occur on the back, neck, hips, and buttocks. OM based on RULA assessment observed that the position of the worker has a value score of 6, which requires further analysis and changes at the earliest. Based on the RULA assessment, this paper recommended the involvement of ergonomics at the place of work to decrease the MSD issues encountered by the operator and make the places of work relaxing. According to the results, the new workplace displays a value score of 3 based on RULA assessment and the final tally was noted to be a satisfactory posture. Thus, the SR method is beneficial for preliminary screening before deploying further assessment of the OM methodology. It is vital for follow-up assessment in order to offer suggestions on the basis of ergonomic risk evaluation.